An In Depth Investigation into the Lion and Sun Symbolism in Iran Flag Prior to 1979 - Zabolinezhad, Hoda (Journal of Ecohumanism, 2025)
After the advent of Islam, the phrase "Zillullah fi al-arz" ("Shadow of God on Earth") replaced the Sassanian expression "Who is the face of the gods." This concept of "Zillullah" remained firmly present in Iranian royal ideology after Islam and continued with full strength until the Qajar era. This research, which is descriptive-analytical in nature and based on library sources, seeks to answer the main question: What symbolic elements underlie the design of the triangular silk textile featuring the Lion and Sun motif (dated 1284 AH / 1242 SH), which was likely used as the first Qajar flag? The "Lion and Sun" emblem of Iran, first minted during the reign of Fath-Ali Shah (1772-1834 CE) and adorning the Iranian flag until 1357 SH (1979 CE), originates from the same ideological background. The lion, depicted reclining without a sword, and the sun, portrayed with a feminine face rising behind the lion—considered the most powerful of animals and the king of the wilderness—symbolize kingship. The radiant sun represents one of the strongest symbols of "Farr" (divine glory) in Sassanian royal tradition (224-651 CE). Thus, the Iranian king, symbolized by the lion with the sun above his head emitting rays of light, is interpreted as the most "Farr" human being. The presence of the Lion and Sun motif on a background adorned with Quranic verses indicates a religious dimension in addition to its symbolic meaning